Case series of filicide: killing own child and drug abuse / Salmi Razali - Razali, Salmi (Centre for Media and Information Warfare Studies, 2017)
Substantial newspaper articles have highlighted the seriousness of filicide or parental child killing in Malaysia. Filicide stems from various interrelated factors and one of the critical but seldom discussed is drug abuse. This study aimed to illustrate the process of how drug abuse could lead to filicide in this country. Data collection involved review of two documents i) forensic psychiatric records from two main psychiatric institutions and ii) transcripts of individual face-to-face interviews with women convicted of filicide incarcerated in five female divisions of prisons in Malaysia. Data was then analysed using thematic analysis to identify the process of how drug abuse has lead to filicide. Drug abuse linked directly or indirectly to filicide. Abusing drug associated with domestic violence and child maltreatment leading to filicide. Drug abuse gave several negative impacts including unemployment, financial difficulty, lack of parental role and family dysfunction that increased the likelihood of mental illnesses which contributed to filicide. By hypnotising women with drugs, women were sexually assaulted, then conceived unwanted baby which ultimately died of abandonment. Every level of society, especially family and service providers such as mental health professionals (psychiatrist, psychologist, counsellors), law enforcers and anti-drug agencies (such National Antidrug Agencies) have to be more vigilant to detect the possibility of filicide among drug abusers